Updated determinations of |V$_{us}$| with tau decays using new recent estimates of radiative corrections for light-meson leptonic decay rates - Alberto Lusiani (SciPost Physics Proceedings)
We update the |V$_{us}$| determinations using the HFLAV 2018 report tau branching fraction results with recent new estimates of the $π\ell2$ and $K\ell2$ radiative corrections. There are minor changes of the central values and uncertainties.